Faktor Determinan yang Berhubungan dengan Risiko Diabetes Melitus Pada Remaja Putri - 'Aabidah, Nabiila Nadziifatul; Wijayanti, Lumastari Ajeng (STIKES Karya Husada Kediri, 2025)
The prevalence of diabetes mellitus (DM) has increased from 10.9%, with 50% of people with diabetes undiagnosed in Indonesia. This article aims to determine the determinants associated with the risk of diabetes mellitus in adolescent girls. The problem focuses on the increasing prevalence of diabetes mellitus (DM), which is now not only experienced by parents but also affects adolescents, especially adolescent girls who are at risk of reproductive disorders due to DM. Data were collected through a descriptive analytical survey with a cross-sectional design, using a questionnaire to 134 adolescent girls selected from a population of 201 people using the Slovin formula. Analysis was performed using the chi-square test and continued with logistic regression using the Backward LR method. The results showed that sweet consumption patterns were the highest risk factor (p = 0.000; CI = 2.01–2.26), followed by obesity, knowledge, physical activity, and information exposure with a significance value of p <0.05 each. This study concluded that these five factors were significantly associated with the risk of diabetes mellitus in adolescent girls. Therefore, promotive and preventive efforts aimed at adolescents are very important to prevent diabetes early.